Social Media, Software Engineering Collaboration Tools and Software Companyâs Performance - Nematova, G. (Springer Verlag, 2020)
Software Engineering (SE), like any other field, is utilizing Web 2.0. Within Web 2.0, Social Media (SM) is changing the landscape of Software Engineering (SE) and has the ability to improve the performance of Software Engineering Organizations (SEO). Regardless of the seeming widespread use of Social Media (SM) in SE, there is still little knowledge about the benefits or risks of SM usage as well as which SM tools could be used to enhance SE Organizationâs performance, and the influence they may show on the quality of software. Furthermore, in order to increase the success rate, organizations have to be able to take advantage of crisis situation as well. However, utilization of SM in CM appears as an under-studied topic and there is an emerging need of compact framework in this domain. Furthermore, so far, academic research conducted on SM, remains incomprehensive regarding its numerous purposes and subsequent influences on organizations. Same is the case for SM utilization in CM. In addition to SM, SE collaboration tools are also a vital source of improving performance. Prior literature indicates towards the need for research work on utilization of Web 2.0, especially SM and other collaboration tools, for CM in SEOs. Hence, there is a need for a thorough research on this topic. The present research aims to examine the role of social media and software engineering collaboration tools for effective crisis management and improved performance of software organizations. Based on extensive literature review and relevant theories, the present research aims to provide a conceptual framework of the use of SM and SE collaboration tools to enhance the performance of software engineering companies. Furthermore, the mediating role of crisis management is also be proposed. Â© 2020, Springer Nature Singapore Pte Ltd.